Can foreign firms bond themselves effectively by renting U.S. securities laws? - Siegel, Jordan (Journal of Financial Economics, 2005)
The study tests the functional convergence hypothesis, which states that foreign firms can leapfrog their countries’ weak legal institutions by listing equities in New York and agreeing to follow U.S. securities law. Evidence shows that the SEC and minority shareholders have not effectively enforced the law against cross-listed foreign firms. Detailed evidence from Mexico further shows that while some insiders exploited this weak legal enforcement with impunity, others that issued a cross-listing and passed through an economic downturn with a clean reputation went on to receive privileged long-term access to outside finance. As compared with legal bonding, reputational bonding better explains the success of cross-listings.